Effects of shyness on interpersonal cognition - AIKAWA, ATSUSHI; KURIBAYASHI, YOSHIMASA (Jikken shakai shinrigaku kenkyū, 1995)
The purpose of this study was to investigate the effect of trait shyness on interpersonal cognition. Twenty seven subjects who were high in a self-rated trait shyness scale and twenty four who were low in it conversed with an unknown opposite-sex partner. The subjects (a) rated their impression of their partner, and (b) guessed the partner's rating for themselves. The partners and observers rated the impression of subjects. The main results were as follows. (a) Shy subjects perceived their partner's impression of the activity-related dimension negatively. (b) Shy subjects guessed that they were perceived negatively by their partners. (c) The discrepancy between shy subject guess and observer rating appeared in two cognitional dimensions. These results were discussed in terms of the possibility of a negative perception bias on the part of shy subjects.